Critique on the bible compilation framework timeline: inclination with the development of Islamic sources - Yaacob, Solehah@Nik Najah Fadilah (University of Malaya, 2018)
There were several attempts by some Jews and Christians to explain how the biblical authors insisted that God dictated the text to Moses. However, later the intellectual journey looks at Bible with commentaries which began at 2nd century in Palestine when the interpretation done in classical commentaries in Aramaic then in Hebrew. However, in 20th century the impact of Orientalist` commentaries pointed out the first chapter of Genesis did not describe a literary sequence. In fact, the commentaries of different centuries from different countries having testimony to the common ground of understanding between them and this process is still not ending until now. According to Avigdor Bonchek the pseudo interpretation is a result of non-depth of understanding on the rules of interpretation. The interpretation must work from the original Hebrew; therefore, he believes that the interpretation does not delve further into the understanding of the original source. However, this is `escapism` typical of the literary sources, due to the major problem of Bible is not the translation itself but the interpretation sources referred. Thus, the paper focuses on some devia tions information in the scriptures either old testament or new testament of the Bible with the inclination of the Islamic sources such as the compilation of Quran and Hadith. Then, an analytical and critical study are using as a methodology approach in paper writing in order to ensure some ideas of verses in Bible were transferred from Islamic sources such as Quran.